Self-Decoupled Quad-Port CPW-Fed Fractal MIMO Antenna With UWB Characteristics - Mian Muhammad Kamal; Binghao Wang; Nosherwan Shoaib; Umair Rafique; Muhammad Inam Abbasi; Muhammad Ramlee Kamarudin (International Journal of Antennas and Propagation)
In this work, a novel fractal multiple-input multiple-output (MIMO) antenna is designed for ultrawideband (UWB) applications. The radiating structure of the MIMO configuration employs a circular fractalradiating structure excited through a modified coplanar waveguide (CPW) feed. The fractal shape is designed by employing small circular rings inside the main circular ring patch element, which led to enhanced impedance bandwidth spanning from 3.15 to 20 GHz with acceptable radiation properties. The results show that the designed antenna has a peak gain of 6.13 dBi and radiation efficiency of > 85% in the operating bandwidth. Moreover, the single-antenna element exhibits stable radiation patterns in the UWB frequency spectrum. For MIMO communication systems, a polarization diversity-based quad-port MIMO antenna is designed. From the designed MIMO antenna configuration, an isolation of > 15 dB is achieved among the radiating elements without the use of any isolation enhancement network. Furthermore, MIMO performance parameters such as envelope correlation coefficient (ECC) of < 0.008, mean effective gain (MEG) of < −3 dB, channel capacity loss (CCL) of < 0.25 bps/Hz, and total active reflection coefficient (TARC) of > 20 dB are obtained from the proposed UWB MIMO antenna.